Neurotoxins subvert the allosteric activation mechanism of SARM1 to induce neuronal loss - Tong Wu; Jian Zhu; Amy Strickland; Kwang Woo Ko; Yo Sasaki; Caitlin B. Dingwall; Yurie Yamada; Matthew D. Figley; Xianrong Mao; Alicia Neiner; A. Joseph Bloom; Aaron DiAntonio; et al. (Cell Reports, 2021)
Summary: SARM1 is an inducible TIR-domain NAD+ hydrolase that mediates pathological axon degeneration. SARM1 is activated by an increased ratio of NMN to NAD+, which competes for binding to an allosteric activating site. When NMN binds, the TIR domain is released from autoinhibition, activating its NAD+ hydrolase activity. The discovery of this allosteric activating site led us to hypothesize that other NAD+-related metabolites might activate SARM1. Here, we show the nicotinamide analog 3-acetylpyridine (3-AP), first identified as a neurotoxin in the 1940s, is converted to 3-APMN, which activates SARM1 and induces SARM1-dependent NAD+ depletion, axon degeneration, and neuronal death. In mice, systemic treatment with 3-AP causes rapid SARM1-dependent death, while local application to the peripheral nerve induces SARM1-dependent axon degeneration. We identify 2-aminopyridine as another SARM1-dependent neurotoxin. These findings identify SARM1 as a candidate mediator of environmental neurotoxicity and suggest that SARM1 agonists could be developed into selective agents for neurolytic therapy.